Optical properties of pentacene and perfluoropentacene thin films. - Hinderhofer, A; Heinemeyer, U; Gerlach, A; Kowarik, S; Jacobs, R; Sakamoto, Y; Suzuki, T; Schreiber, F (2007)
The optical properties of pentacene (PEN) and perfluoropentacene (PFP) thin films on various SiO(2) substrates were studied using variable angle spectroscopic ellipsometry. Structural characterization was performed using x-ray reflectivity and atomic force microscopy. A uniaxial model with the optic axis normal to the sample surface was used to analyze the ellipsometry data. A strong optical anisotropy was observed, and enabled the direction of the transition dipole of the absorption bands to be determined. Furthermore, comparison of the optical constants of PEN and PFP thin films with the absorption spectra of the monomers in solution shows significant changes due to the crystalline environment. Relative to the monomer spectrum, the highest occupied molecular orbital to lowest unoccupied molecular orbital transition observed in PEN (PFP) thin film is reduced by 210 meV (280 meV). A second absorption band in the PFP thin film shows a slight blueshift (40 meV) compared to the spectrum of the monomer with its transition dipole perpendicular to that of the first absorption band.